A complete volume profile for the reversible binding of camphor to cytochrome P450cam - Franke, Alicja; Schlichting, Ilme (Journal of biological inorganic chemistry, 2012)
The effect of pressure on the kinetics and thermodynamics of the reversible binding of camphor to cytochrome P450cam was studied as a function of the K+ concentration. The determination of the reaction and activation volumes enabled the construction of the first complete volume profile for the reversible binding of camphor to P450cam. Although the volume profiles constructed for the reactions conducted at low and high K+ concentrations are rather similar, and both show a drastic volume increase on going from the reactant to the transition state and a relatively small volume change on going from the transition to the product state, the position of the transition state is largely affected by the K+ concentration in solution. Similarly, the activation volume determined for the dissociation of camphor is influenced by the presence of K+, which reflects changes in the ease of water entering the active site of camphor-bound P450cam that depends on the K+ concentration. Careful analysis of the components that contribute to the observed volume changes allowed the estimation of the total number of water molecules expelled to the bulk solvent during the binding of camphor to P450cam and the subsequent spin transition. The results are discussed in reference to other studies reported in the literature that deal with the kinetics and thermodynamics of the binding of camphor to P450cam under various reaction conditions.
Gesehen am 19.09.2018
Im Titel ist cam tiefgestellt